2017
DOI: 10.1016/j.aca.2016.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Microplasma-based flowing atmospheric-pressure afterglow (FAPA) source for ambient desorption-ionization mass spectrometry

Abstract: A new direct-current microplasma-based flowing atmospheric pressure afterglow (FAPA) source was developed for use in ambient desorption-ionization mass spectrometry. The annular-shaped microplasma is formed in helium between two concentric stainless-steel capillaries that are separated by an alumina tube. Current-voltage characterization of the source shows that this version of the FAPA operates in the normal glow-discharge regime. A glass surface placed in the path of the helium afterglow reaches temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The formation of [M + O + H] + was due to the oxidation of 8-hydroxyquinoline during ionization. Such oxidation reaction was commonly observed for compounds containing the aromatic group in a plasma-based ionization process such as LTP and flowing atmospheric pressure afterglow (FAPA) . No reduction species formed by dihydrogenation was detected.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The formation of [M + O + H] + was due to the oxidation of 8-hydroxyquinoline during ionization. Such oxidation reaction was commonly observed for compounds containing the aromatic group in a plasma-based ionization process such as LTP and flowing atmospheric pressure afterglow (FAPA) . No reduction species formed by dihydrogenation was detected.…”
Section: Resultsmentioning
confidence: 87%
“…Such oxidation reaction was commonly observed for compounds containing the aromatic group in a plasma-based ionization process such as LTP 28 and flowing atmospheric pressure afterglow (FAPA). 29 No reduction species formed by dihydrogenation was detected. This compared well with previous studies in which reduction by dihydrogenation was observed for arenes using LTP but not detected for aromatic heterocycle compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…This raises the need for more detailed investigation, e.g., by computer modeling, to reveal the dominant ionization mechanisms. Moreover, it may help to optimize the setup geometry, such as the so-called μ-FAPA . By providing details on the gas flow patterns, computer modeling may, for instance, explain the effect of applying a discontinuous helium gas flow within the FAPA source for the analysis of gaseous samples, leading to lower helium consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Although the plasma‐based techniques share similar chemical and chemi‐ionization reactions, that is, Penning ionization, electron capture/abstraction, and proton transfer, to produce ions from the laser‐desorbed analytes, they are diverse in the configuration of the ion sources, the mechanism of plasma gas discharge, the parameters of the desorption laser, and the way introducing the desorbed species to the ion sources. Due to the metastable/radical‐induced ionization mechanism, the plasma‐based two‐step desorption/ionization methodologies were limited to analysis of molecules with mass weight lower than 1000 Da, but minimization of the size of the discharge chamber has successfully extended the mass range to above 2000 Da (Zeiri et al, 2017). The following sections provide an overview of the plasma‐based postionization techniques and their applications in biological analysis.…”
Section: Laser Desorption/ablation Coupled To Ambient Ionization In Bioapplicationsmentioning
confidence: 99%